Everyday Life, Colloquiality and Reflexivity as the Existential Determinants of Advicory Services in the (Post)Modern World - Teusz, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article is an attempt to describe everyday life, colloquiality and reflexivity as existential determinants of advisory services in the (post)modern culture. The situation of advisory services as a specific social relationship occurring between two entities – an adviser and a person who is given advice (its aim is to solve particular problems from his/her life) – has been presented by reference to these three categories. Particular emphasis has been placed on emphasizing the importance of reflexive interpretation and understanding in advisory services to show their role in the constituting of subjective self.
Keywords: advisory services; colloquiality; counseling; everyday life; reflexivity